Factors affecting dental students' postgraduate plans: A multi‐site study. Issue 2 (23rd September 2021) - Harrison, James L.; Platia, Christina L.; Ferreira, Leticia; Soh, Margaret; Bugueño, Juan M.; Thompson, Tammy L.; Quock, Ryan L.; Finkelman, Matthew; Uzel, Naciye G.
Abstract: Purpose: This multi‐site study examined dental students' postgraduate plans and factors affecting them, perceptions of pathways with the best future, and whether those postgraduate plans changed during dental school. Methods: An online survey was made available to all four dental classes (2018, 2019, 2020, and 2021) and advanced standing/international dental students at eight US dental schools. The survey questionnaire consisted of two parts: (1) 14 questions pertaining to demographic information and (2) 11 questions pertaining to career path choices and possible influencing factors. Results: Overall response rate was approximately 38.4% (1459/3800). For those responding 34.0% planned to enroll in a general dentistry residency, followed by associate dentist in a private practice (31.4%), and specialty residency (17.6%). Quality of life, to increase knowledge/clinical skills, and intellectual satisfaction were most often rated extremely important factors; Influence of family members in dentistry and prestigious specialty received the most responses of not important. General dentistry was perceived to have the best future in terms of overall impact on the profession, potential for positive impact on patient's quality of life, and personal quality of life; oral and maxillofacial surgery was believed to have the best future in terms of salary. Students changed their postgraduate plan during dental school 43.0% of the time, with race ( p  = 0.006) and year of progress toward degree ( p  < 0.001) being significant associations. Conclusions: General dentistry remains the most popular pathway. Many dental students change their plans during dental school; a better understanding of these trends and contributing factors may aid development of practice readiness curricula.